Cost-effectiveness analysis of pembrolizumab plus chemotherapy for previously untreated metastatic non-small cell lung cancer in the USA - Xiaohui Zeng; Xiaomin Wan; Liubao Peng; Ye Peng; Fang Ma; Qiao Liu; Chongqing Tan (BMJ Open)
Objectives Evaluating the cost-effectiveness of pembrolizumab plus standard chemotherapy in the first-line setting for patients with metastatic non-small cell lung cancer (NSCLC) from the US payer perspective.Design A Markov model was constructed to analyse the cost-effectiveness of pembrolizumab plus chemotherapy in the first-line treatment of metastatic NSCLC. Health outcomes were estimated in quality-adjusted life-years (QALYs). The cost information was from Medicare in 2018. One-way and probabilistic sensitivity analyses examined the impact of uncertainty and assumptions on the results.Setting The US payer perspective.Participants A hypothetical US cohort of patients with previously untreated metastatic nonsquamous NSCLC without EGFR or ALK mutations.Interventions Pembrolizumab plus chemotherapy versus chemotherapy.Primary outcome measures Costs, QALYs, incremental cost-effectiveness ratio (ICER) of pembrolizumab plus chemotherapy expressed as cost per QALY gained compared with chemotherapyResults The base case analysis demonstrated that pembrolizumab plus chemotherapy provided an additional 0.78 QALYs at incremental cost of $151 409, resulting in an ICER of $194 372/QALY. ICER for pembrolizumab plus chemotherapy was >$149 680/QALY in all of our univariable and probabilistic sensitivity analyses.Conclusions Pembrolizumab in addition to chemotherapy provides modest incremental benefit at high incremental cost per QALY for the treatment of previously untreated metastatic NSCLC.